Use of 68Ga DOTATATE, a new molecular imaging agent, for neuroendocrine tumors. Issue 1 (2nd January 2020) - LeBlanc, Raymond Andrew; Oza, Umesh D.; Hayden, Ryan; Fanous, Hanna
Abstract: Neuroendocrine tumors (NET), such as insulinomas and carcinoid tumors, can be challenging to diagnose since patients often present with vague symptoms. Adding to the challenge, these tumors are often occult on typical cross-sectional imaging modalities. Because of these challenges, there has been an increase in the utilization of radiopharmaceuticals that take advantage of specific receptors expressed by NET. Among the multiple radiopharmaceuticals that can be used, 68 Ga DOTATATE is emerging as the most sensitive and specific imaging agent. We present a case where 68 Ga DOTATATE was used to diagnose a well-differentiated neuroendocrine tumor.